Assessing and managing symptom burden and quality of life in primary sclerosing cholangitis patients. (1st February 2021) - McCain, Josiah D.; Chascsa, David M.; Lindor, Keith D.
ABSTRACT: Introduction : Primary sclerosing cholangitis (PSC) is a progressive disease of the bile ducts for which there is no cure. As no therapy has proven to delay this progression, the current focus for these patients is symptom management. In the same vein, the screening for and prevention of diseases for which these patients carry increased risk is an effective part of high-yield care. Areas Covered : A literature search was conducted using the National Center for Biotechnology Information (NCBI) database at the U.S. National Library of Medicine (NLM). Herein is reviewed that literature with special attention to symptom assessment and medical therapies as well as associated disease and screening strategies for patients with PSC. Additionally, some of the previous therapies future directions of treatment are explored. Expert Opinion : Efforts to alter the progression of this disease by targeting the inflammatory process have not produced meaningful results. The limited success of antimicrobial agents raises the question of the role of dysbiosis in PSC and marks a new potential target for therapies to be studied. However, as in many progressive diseases of the liver, fibrosis of the organ remains the irreversible step, and until effective anti-fibrotic agents are developed a definitive cure for PSC may remain elusive.